Collagen-tamarind gum composite fiber and preparation method thereof

By combining collagen and tamarind glue and using wet spinning technology to prepare collagen-tamarind glue composite fibers, the problems of insufficient biosafety and poor mechanical properties of collagen composite fibers are solved, and the preparation of high-quality fibers and green and environmentally friendly production are achieved.

CN119593079AActive Publication Date: 2025-03-11DONGHUA UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411900980.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

In the existing collagen spinning technology, the biosafety of collagen composite fibers is insufficient and the mechanical properties are poor, making it difficult to form high-quality continuous wire strips.

Method used

Collagen-tamarinate composite fiber is prepared by swelling, defoaming, wet spinning and multi-stage cleaning bath. This method avoids the use of organic solvents, forms interpenetrating network structures and hydrogen bonds, and enhances the mechanical properties of the fibers.

Benefits of technology

It improves the breaking strength of collagen fibers, ensures that its mechanical properties meet the application requirements of multiple fields, and simplifies the preparation process, improves production efficiency, and complies with the concept of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593079A_ABST
    Figure CN119593079A_ABST
Patent Text Reader

Abstract

The invention provides a collagen-tamarind gum composite fiber and a preparation method thereof, and belongs to the technical field of composite fibers. The preparation method comprises the following steps: swelling a collagen stock solution to obtain a collagen dispersion liquid, and adding tamarind gum and a cross-linking agent to prepare a collagen-tamarind gum dispersion liquid; then, the collagen-tamarind gum dispersion liquid is subjected to defoaming treatment, and a collagen-tamarind gum spinning solution is prepared; finally, the collagen-tamarind gum spinning solution is extruded into a first coagulating bath through wet spinning, and the collagen-tamarind gum composite fiber is prepared through traction, second coagulating bath and stretching. In the collagen-tamarind gum composite fiber, tamarind gum and collagen molecular chains form an interpenetrating network structure and form hydrogen bonds, the mechanical property of the collagen fiber can be effectively enhanced, the breaking strength of the collagen-tamarind gum composite fiber is larger than 1.5 cN / dtex, and the collagen-tamarind gum composite fiber meets the application requirements of many fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite fibers, and in particular to a collagen-tamarind gum composite fiber and a preparation method thereof. Background Art

[0002] Collagen is a natural protein that is widely found in connective tissues such as skin, bones, cartilage, teeth, tendons, ligaments and blood vessels of animals. It is the main structural protein of these tissues. Collagen can be divided into many types according to its structure and function. The most common type is type I collagen, which accounts for about 80% to 90% of the total collagen content. Collagen has excellent biocompatibility, degradability and biological activity, and has broad application prospects.

[0003] At present, the development of collagen spinning technology faces two major challenges: first, the simple collagen spinning solution has poor spinnability and is difficult to form continuous filaments, which affects the smooth spinning process and product quality; second, the obtained fibers have low crystallinity, insufficient strength, easy brittle fracture, and limited practicality. To solve these problems, researchers have tried to blend collagen with other materials (such as chitosan, polyvinyl alcohol, and polyacrylonitrile), but the composite fibers have deficiencies in biosafety. At the same time, the mainstream process for preparing collagen filaments uses solvents (such as hexafluoroisopropanol and other fluoroalcohols) to dissolve collagen and then wet spin, but it destroys the aggregated structure of natural collagen, resulting in poor mechanical properties, thermal stability, and structural stability of the fibers. Therefore, how to improve spinning efficiency and fiber quality while maintaining collagen performance has become a key issue that needs to be urgently addressed in current research. Summary of the invention

[0004] The purpose of the present invention is to provide a collagen-tamarind gum composite fiber and a preparation method thereof, so as to solve the problems of insufficient biological safety and poor mechanical properties of the collagen composite fiber in the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing collagen-tamarind gum composite fibers, comprising the following steps:

[0007] S1: swelling the collagen stock solution to obtain a collagen dispersion, adding tamarind gum and a cross-linking agent to prepare a collagen-tamarind gum dispersion;

[0008] S2: degassing the collagen-tamarind gum dispersion to obtain a collagen-tamarind gum spinning solution;

[0009] S3: Extruding the collagen-tamarind gum spinning solution into the first coagulation bath by wet spinning, and then pulling, placing in the second coagulation bath, and stretching to obtain the collagen-tamarind gum composite fiber.

[0010] Preferably, in step S1, the concentration of collagen in the collagen dispersion is 1-3 wt %.

[0011] Preferably, in step S1, the swelling is carried out in an acidic solution, wherein the acidic solution comprises a hydrochloric acid solution or an acetic acid solution.

[0012] Preferably, in step S1, tamarind gum and a cross-linking agent are added and stirred in an ice-water bath for 3 to 6 hours to prepare a collagen-tamarind gum dispersion; based on the mass of collagen in the collagen dispersion, the amount of tamarind gum added is 5 to 30%, and the amount of the cross-linking agent added is 0.03 to 0.1%; the cross-linking agent comprises glutaraldehyde, genipin or 1-ethyl-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide.

[0013] Preferably, in step S3, the process parameters of wet spinning are: extrusion pressure of 0.3-0.5 MPa, extrusion speed of 0.3-0.6 mL / min, spinning temperature of 10-30° C., and spinning speed of 0.6-2 m / min.

[0014] Preferably, in step S3, the first coagulation bath is a polyethylene glycol solution, wherein the concentration of the polyethylene glycol solution is 10-25wt% and the pH value is 9-13; the second coagulation bath is an inorganic salt solution, wherein the concentration of the inorganic salt solution is 20-50wt%.

[0015] Preferably, the polyethylene glycol in the polyethylene glycol solution comprises one or more of PEG4000, PEG8000, PEG10000 and PEG20000; and the inorganic salt in the inorganic salt solution comprises sodium salt, potassium salt or ammonium salt.

[0016] Preferably, in step S3, the stretching ratio during stretching is 1.3 to 1.5:1.

[0017] The present invention also provides a collagen-tamarind gum composite fiber prepared by the preparation method of the collagen-tamarind gum composite fiber.

[0018] Preferably, the breaking strength of the collagen-tamarind gum composite fiber is 1.5-2.5 cN / dtex.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention uses collagen and tamarind gum as raw materials to prepare collagen-tamarind gum composite fibers. The added tamarind gum can form an interpenetrating network structure and hydrogen bonds with the collagen molecular chains, which can effectively enhance the mechanical properties of the collagen fibers. The breaking strength of the collagen-tamarind gum composite fibers is greater than 1.5 cN / dtex, which meets the application requirements in many fields.

[0021] (2) The preparation method of the collagen-tamarind gum composite fiber provided by the present invention is simple, easy to operate, mild in preparation conditions, and high in production efficiency. Collagen fibers of different diameters can be designed according to application requirements, and large-scale production can be achieved.

[0022] (3) The present invention avoids using organic solvents in the process of preparing collagen-tamarind gum composite fibers, and the production process complies with the concept of green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the interpenetrating network structure of the collagen-tamarind gum composite fiber of the present invention;

[0024] Figure 2 is a scanning electron microscope image of the collagen-tamarind gum composite fiber of Example 1;

[0025] Figure 3 This is a diagram of the mechanical properties of the collagen-tamarind gum composite fiber of Example 1. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing collagen-tamarind gum composite fibers, comprising the following steps:

[0027] S1: swelling the collagen stock solution to obtain a collagen dispersion, adding tamarind gum and a cross-linking agent to prepare a collagen-tamarind gum dispersion;

[0028] S2: degassing the collagen-tamarind gum dispersion to obtain a collagen-tamarind gum spinning solution;

[0029] S3: Extruding the collagen-tamarind gum spinning solution into the first coagulation bath by wet spinning, and then pulling, placing in the second coagulation bath, and stretching to obtain the collagen-tamarind gum composite fiber.

[0030] In the present invention, it is preferred to extract collagen before preparing collagen stock solution. The collagen extraction method is: soaking the collagen raw material in an alkaline solution, washing it after soaking, and finally placing it in a wall breaking machine, adding ice water and beating it evenly to obtain collagen.

[0031] In the present invention, the concentration of the alkaline solution is 5 to 15 wt %; the soaking time is 6 to 10 h; and the cleaning is preferably performed using deionized water.

[0032] In the present invention, the collagen raw material comprises bovine hide, bovine tendon or bovine ligament.

[0033] In the present invention, in step S1, the concentration of collagen in the collagen dispersion is 1 to 3 wt%, preferably 1.5 to 2.5 wt%.

[0034] In the present invention, in step S1, swelling is performed in an acidic solution, wherein the acidic solution comprises a hydrochloric acid solution or an acetic acid solution, and the pH value of the acidic solution is 2-3.

[0035] In the present invention, in the step S1, tamarind gum and a cross-linking agent are added and stirred in an ice-water bath for 3 to 6 hours to prepare a collagen-tamarind gum dispersion; based on the mass of collagen in the collagen dispersion, the amount of tamarind gum added is 5 to 30%, preferably 10 to 20%; the amount of the cross-linking agent added is 0.03 to 0.1%, preferably 0.04 to 0.09%, and more preferably 0.06%.

[0036] In the present invention, the cross-linking agent comprises glutaraldehyde, genipin or 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) / N-hydroxysuccinimide (NHS), preferably glutaraldehyde or genipin.

[0037] In the present invention, the collagen-tamarind gum dispersion is preferably filtered before the degassing treatment to remove insoluble or poorly soluble substances in the dispersion.

[0038] In the present invention, in step S3, the process parameters of wet spinning are: extrusion pressure of 0.3-0.5 MPa, extrusion speed of 0.3-0.6 mL / min, spinning temperature of 10-30° C., and spinning speed of 0.6-2 m / min.

[0039] In the present invention, in step S3, the first coagulation bath is a polyethylene glycol solution, wherein the concentration of the polyethylene glycol solution is 10 to 25 wt%, preferably 15 to 20 wt%, and the pH value is 9 to 13, preferably 10 to 12; the second coagulation bath is an inorganic salt solution, wherein the concentration of the inorganic salt solution is 20 to 50 wt%, preferably 30 to 40 wt%, and further preferably 30 to 35 wt%.

[0040] In the present invention, collagen-tamarind gum spinning solution is injected into an alkaline coagulation bath, and coagulation will occur immediately to form nascent fibers. In the process of fiber being pulled, a bidirectional diffusion phenomenon occurs between the nascent fibers and the coagulation bath: the moisture inside the fiber diffuses into the solution, and the solute in the solution penetrates into the inside of the fiber, and this process prompts the nascent fibers to gradually coagulate and shape. When using polyethylene glycol solution, since it is a polymer solution, it has a certain viscosity, and can provide appropriate resistance to allow the nascent fibers to have a certain stretch, which is conducive to fiber molding. The inorganic salt solution shows a strong coagulation performance, ensures that the nascent fibers are completely coagulated, and effectively prevents the problem of paralleling and adhesion that may occur in the collagen-tamarind gum composite fiber during the collection process, and the subsequent multi-stage cleaning bath can ensure that the coagulation bath in the nascent fibers is clean, and the high concentration of ethanol solution can help remove moisture.

[0041] In the present invention, the polyethylene glycol in the polyethylene glycol solution comprises one or more of PEG4000, PEG8000, PEG10000 and PEG20000, preferably one or more of PEG8000, PEG10000 and PEG20000, and more preferably PEG8000; the inorganic salt in the inorganic salt solution comprises sodium salt, potassium salt or ammonium salt.

[0042] In the present invention, the sodium salt includes sodium chloride, sodium sulfate, sodium carbonate or sodium nitrate; the potassium salt is preferably potassium chloride, potassium sulfate, potassium carbonate or potassium nitrate; the ammonium salt is ammonium chloride, ammonium sulfate, ammonium carbonate or ammonium nitrate.

[0043] In the present invention, the stretching is preferably preceded by a clean water bath, wherein the clean water bath comprises four sections, namely clean water, 30% ethanol solution, 60% ethanol solution, and 90% ethanol solution.

[0044] In the present invention, in the step S3, the stretching ratio during stretching is 1.3 to 1.5:1, preferably 1.3:1.

[0045] The present invention also provides a collagen-tamarind gum composite fiber prepared by the preparation method of the collagen-tamarind gum composite fiber.

[0046] In the present invention, the breaking strength of the collagen-tamarind gum composite fiber is 1.5-2.5 cN / dtex.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] The collagen extraction method used in the embodiment of the present invention is as follows: soak the cowhide in a 5wt% NaOH solution to remove fat from the collagen raw material for 6 hours; take out the collagen raw material after the fat is removed, remove the sodium hydroxide solution with deionized water, place it in a wall breaking machine, add ice water and stir evenly to obtain 8wt% bovine collagen stock solution for later use.

[0049] Example 1

[0050] The bovine collagen stock solution is placed in a hydrochloric acid solution (pH 2) for full swelling to prepare a collagen dispersion with a concentration of 1.5wt% and a pH of 2, tamarind gum (added amount is 10%) and glutaraldehyde cross-linking agent (added amount is 0.03%) are added, and stirred for 6 hours in an ice-water bath to obtain a collagen-tamarind gum dispersion, which is filtered through a filter device and then centrifuged for degassing at a rotation speed of 8000rpm and a centrifugal time of 10 minutes to obtain a collagen-tamarind gum spinning solution.

[0051] The collagen-tamarind gum spinning solution is extruded through a wet spinning device (wherein the aperture of the spinneret is 0.2 mm, the aspect ratio is 60, the extrusion pressure is 0.4 MPa, the extrusion speed is 0.5 mL / min, the spinning temperature is 20° C., and the spinning speed is 1.0 m / min) into a PEG8000 solution (concentration is 20wt%, pH=12), and then drawn into a 30wt% ammonium sulfate solution, and then sequentially washed with deionized water, 30% ethanol solution, 60% ethanol solution, and 90% ethanol solution, and finally stretched at a stretching ratio of 1.3:1, and finally dried at a temperature of 40° C. to obtain a collagen-tamarind gum composite fiber.

[0052] Example 2

[0053] The difference from Example 1 is that the added amount of tamarind gum is 20%, and other conditions are the same.

[0054] Example 3

[0055] The bovine collagen stock solution was placed in a hydrochloric acid solution (pH 2) for full swelling to prepare a collagen dispersion with a concentration of 2.0wt% and a pH of 2, tamarind gum (added amount of 20%) and glutaraldehyde cross-linking agent (added amount of 0.06%) were added, and stirred for 6 hours in an ice-water bath to obtain a collagen-tamarind gum dispersion, which was filtered through a filtration device and then centrifuged for degassing at a rotation speed of 8000rpm and a centrifugal time of 10 minutes to obtain a collagen-tamarind gum spinning solution.

[0056] The collagen-tamarind gum spinning solution is extruded through a wet spinning device (wherein the aperture of the spinneret is 0.2 mm, the aspect ratio is 60, the extrusion pressure is 0.4 MPa, the extrusion speed is 0.5 mL / min, the spinning temperature is 20° C., and the spinning speed is 1.0 m / min) into a PEG8000 solution (concentration is 20wt%, pH=12), and then drawn into a 30wt% ammonium sulfate solution, and then sequentially washed with deionized water, 30% ethanol solution, 60% ethanol solution, and 90% ethanol solution, and finally stretched at a stretching ratio of 1.3:1, and finally dried at a temperature of 40° C. to obtain a collagen-tamarind gum composite fiber.

[0057] Example 4

[0058] The difference from Example 3 is that the concentration of collagen in the collagen dispersion is 2.5 wt %, the amount of cross-linking agent glutaraldehyde added is 0.09%, and other conditions are the same.

[0059] Example 5

[0060] The difference from Example 3 is that the cross-linking agent is genipin, the added amount of genipin is 0.06%, and other conditions are the same.

[0061] Example 6

[0062] The difference from Example 3 is that the concentration of the PEG8000 solution is 15 wt %, and the other conditions are the same.

[0063] Example 7

[0064] The difference from Example 3 is that the concentration of the ammonium sulfate solution is 35 wt %, and other conditions are the same.

[0065] Example 8

[0066] The difference from Example 3 is that the stretching ratio is 1.5:1, and other conditions are the same.

[0067] Comparative Example 1

[0068] The bovine collagen stock solution was placed in a hydrochloric acid solution (pH 2) for full swelling to prepare a collagen dispersion with a concentration of 1.5wt% and a pH of 2. Glutaraldehyde crosslinking agent (added amount was 0.03%) was added and stirred for 6 hours in an ice-water bath to obtain a collagen dispersion. The dispersion was filtered through a filter device and then centrifuged for degassing at a rotation speed of 8000rpm and a centrifugal time of 10 minutes to obtain a collagen spinning solution.

[0069] The collagen spinning solution was extruded through a wet spinning device (wherein the aperture of the spinneret was 0.2 mm, the aspect ratio was 60, the extrusion pressure was 0.4 MPa, the extrusion speed was 0.5 mL / min, the spinning temperature was 20°C, and the spinning speed was 1.0 m / min) into a PEG8000 solution (concentration was 20wt%, pH=12), and then pulled into a 30wt% ammonium sulfate solution, and then washed in sequence with deionized water, 30% ethanol solution, 60% ethanol solution, and 90% ethanol solution, and finally stretched at a stretching ratio of 1.3:1, and finally dried at 40°C to obtain collagen fibers.

[0070] Performance test: The mechanical properties of the collagen-tamarind gum composite fibers prepared in Examples 1 to 8 and the collagen fibers of Comparative Example 1 were tested using a multifilament yarn strength meter. Test method: A multifilament strength tester (multifilament A0-3000cN) was used to test the mechanical properties of the fibers, with a clamping distance of 200mm, a stretching speed of 250mm / min, a pre-tension of 5cN, 10 groups of valid data were obtained and the average value was taken. The test results are shown in Table 1.

[0071] Table 1 Spinning process parameters and composite fiber performance test results of Examples 1 to 8 and Comparative Example 1

[0072]

[0073] It can be seen from Table 1 that the addition of tamarind gum can effectively enhance the mechanical properties of collagen fibers, and the breaking strength of collagen-tamarind gum composite fibers is greater than 1.5 cN / dtex.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing collagen-tamarind gum composite fiber, characterized in that: The steps include: S1: swelling the collagen stock solution to obtain a collagen dispersion, adding tamarind gum and a cross-linking agent to prepare a collagen-tamarind gum dispersion; S2: degassing the collagen-tamarind gum dispersion to obtain a collagen-tamarind gum spinning solution; S3: Extruding the collagen-tamarind gum spinning solution into the first coagulation bath by wet spinning, and then pulling, placing in the second coagulation bath, and stretching to obtain the collagen-tamarind gum composite fiber.

2. The method for preparing the collagen-tamarind gum composite fiber according to claim 1, characterized in that: In the step S1, the concentration of collagen in the collagen dispersion is 1-3 wt %.

3. The method for preparing the collagen-tamarind gum composite fiber according to claim 1 or 2, characterized in that: In the step S1, swelling is performed in an acidic solution, wherein the acidic solution comprises a hydrochloric acid solution or an acetic acid solution.

4. The method for preparing the collagen-tamarind gum composite fiber according to claim 3, characterized in that: In the step S1, tamarind gum and a cross-linking agent are added and stirred in an ice-water bath for 3 to 6 hours to prepare a collagen-tamarind gum dispersion; based on the mass of collagen in the collagen dispersion, the added amount of tamarind gum is 5 to 30%, and the added amount of the cross-linking agent is 0.03 to 0.1%; the cross-linking agent comprises glutaraldehyde, genipin or 1-ethyl-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide.

5. The method for preparing the collagen-tamarind gum composite fiber according to claim 1, 2 or 4, characterized in that: In the step S3, the process parameters of wet spinning are: extrusion pressure of 0.3-0.5 MPa, extrusion speed of 0.3-0.6 mL / min, spinning temperature of 10-30° C., and spinning speed of 0.6-2 m / min.

6. The method for preparing the collagen-tamarind gum composite fiber according to claim 5, characterized in that: In step S3, the first coagulation bath is a polyethylene glycol solution, wherein the concentration of the polyethylene glycol solution is 10-25 wt % and the pH value is 9-13; the second coagulation bath is an inorganic salt solution, wherein the concentration of the inorganic salt solution is 20-50 wt %.

7. The method for preparing the collagen-tamarind gum composite fiber according to claim 6, characterized in that: The polyethylene glycol in the polyethylene glycol solution includes one or more of PEG4000, PEG8000, PEG10000 and PEG20000; the inorganic salt in the inorganic salt solution includes sodium salt, potassium salt or ammonium salt.

8. The method for preparing the collagen-tamarind gum composite fiber according to claim 3, 4 or 7, characterized in that: In the step S3, the stretching ratio during stretching is 1.3 to 1.5:

1.

9. Collagen-tamarind gum composite fiber obtained by the preparation method of collagen-tamarind gum composite fiber according to any one of claims 1 to 8.

10. The collagen-tamarind gum composite fiber according to claim 9, characterized in that: The breaking strength of the collagen-tamarind gum composite fiber is 1.5-2.5 cN / dtex.

Citation Information

Patent Citations

  • Preparation method for constructing composite hydrogel by compounding collagen base and nonionic polysaccharide

    CN106496608A

  • Preparation method of collagen fibers

    CN108977912A

  • Preparation method of in-situ cross-linked collagen fiber

    CN109385682A

  • Method for preparing collagen fiber through wet spinning

    CN111501121A

  • Collagen filament with collagen microfiber structure and preparation method thereof

    CN115559009A